2000
DOI: 10.1071/ch00060
|View full text |Cite
|
Sign up to set email alerts
|

Powder diffraction studies of synthetic calcium and lead apatites

Abstract: The crystal structures of M10(PO4)6X2, where M = Ca or Pb and X = OH¯, F¯, Cl¯ or Br¯, have been determined by Rietveld refinement of powder synchrotron X-ray and neutron diffraction data. All the compounds are hexagonal with space group P 63/m. For the calcium compounds, the lattice parameters are a = 9.4302(5), 9.3475(3), 9.5902(6), 9.6482(6) and c = 6.8911(2), 6.8646(1), 6.7666(2), 6.7788(2) Å, for X = OH¯, F¯, Cl¯, Br¯, respectively. For the lead compounds, the corresponding lattice parameters are a = 9.86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 0 publications
12
51
0
1
Order By: Relevance
“…It has been argued that polarization due to sp hybridization in Pb2 could explain dislocations of halogen ions in the X channel [20]. However, in agreement with DFT calculations [5,8], we have found no significant 6s−6p hybridization in the lead apatites.…”
Section: Band Structuresupporting
confidence: 85%
“…It has been argued that polarization due to sp hybridization in Pb2 could explain dislocations of halogen ions in the X channel [20]. However, in agreement with DFT calculations [5,8], we have found no significant 6s−6p hybridization in the lead apatites.…”
Section: Band Structuresupporting
confidence: 85%
“…Moreover, its properties like osteoconductivity, nontoxicity, noninflammatory behaviour, and non-immunogenicity makes it applicable as bone implant, in drug dlivery system and in catalysis. Apart from this, HAP is also reported having two crystalline structures, i. e., hexagonal and monoclinic [4,5]. Nowadays, the influence of the inclusion of trace elements or dopants on the physical and/or chemical properties of the bio-ceramics is of interest in the nano and bulk forms.…”
Section: Introductionmentioning
confidence: 97%
“…Based on the known structural composition of hydroxyapatite, similarities to glass and other ceramics we therefore reasoned that a reaction with silanes should be possible. Previously we had shown that the amount of 125 I-ubiquitin nonspecifically bound to the porous hydroxyapatite ceramic Endobon [7] (Merck AG Darmstadt, density 1.289 g/cm 3 , $100 % HAP [1]) can be increased from 6 lg/ g to 24-30 lg/g by covalently linking it via a reaction with 3-aminopropyltriethoxysilane (APS) followed by carbonyldiimidazole (CDI) [8]. A similar reaction scheme has been employed by our group for several years for coupling rhBMP-2 to titanium surfaces [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Bone is composed to $ 60 % of hydroxyapatite (HAP, see [1]), which in its crystalline form has the chemical composition Ca 10 (PO 4 ) 6 (OH) 2 (see [2][3][4]). Hydroxyapatite has a very low solubility product of 2.34 x 10 -59 with a calculated dissociation constant of $0.44 lM [5].…”
Section: Introductionmentioning
confidence: 99%